TINDAK PIDANA PERDAGANGAN ORANG (HUMAN TRAFFICKING) KHUSUSNYA TERHADAP PEREMPUAN DAN ANAK : SUATU PERMASALAHAN DAN PENANGANANNYA DI KOTA SEMARANG - Wulandari, Cahya; Wicaksono, Sonny Saptoajie (Yustisia, 2014)
The rise ofhuman trafficking casesinIndonesia, raisesits own concerns. Various cases ofhuman trafficking is happening right now based on reports in the mass media and electronic media as well as some research show human trafficking especially in women and children need serious attention. Trafficking of women and children that occurred in Indonesia usually for prostitution, pornography, begging and domestic servants. This studyaims to determine the factors that cause the occurrence of women and children trafficking and find difficulties in handling cases of trafficking in women and children. This research was conducted with the juridical sociological analytical descriptive. Primary data and secondary data collected through free guided interview techniques, library research and documentation. Determination ofthe respondents conducted bypuporsive sampling. Data that has been collected analyzed qualitatively.The study concluded that: (a) the factors that influencehuman trafficking especiallyof women and children in general because of poverty, lack of education, lack of information andare in thesocio-cultural conditions that are less favorable for their development. (b) Constraints in the handling ofcases ofhuman trafficking apart due to lack ofknowledge ofthe law enforcement in implementing UU No.21 Year2007 on Pemberantasan Tindak Pidana Perdagangan Orang is also due tothe lack ofcross-sectoral coordinationin the handling ofthe case.